1977
DOI: 10.1002/jbm.820110409
|View full text |Cite
|
Sign up to set email alerts
|

New prospects for a prolonged functional life‐span of artificial hip joints by using the material combination polyethylene/aluminium oxide ceramic/metal

Abstract: Investigations over the years have shown that the mirror-finished Al2O3 ceramic is a much more suitable frictional counterpart to ultrahigh molecular weight (UHMW) polyethylene than metal. Despite the extremely gread hardness difference between polyethylene and Al2O3 ceramic, a considerable lower wear rate is obtained for the polyethylene socked with this new low-friction material combination. The unexpectedly favorable tribological behavior of this ceramic material in contact with polyethylene may be attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(57 citation statements)
references
References 6 publications
0
52
0
2
Order By: Relevance
“…The advantage of using a ceramic head in combination with a polyethylene liner is a reduction in the wear rate compared with that of a metal head as an articulating partner. [28][29][30] Additionally, the method of polyethylene manufacture should be considered. In 1985, Sulzer Orthopedics obtained an essentially homogenous calcium stearate-free polyethylene with substantially improved wear behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of using a ceramic head in combination with a polyethylene liner is a reduction in the wear rate compared with that of a metal head as an articulating partner. [28][29][30] Additionally, the method of polyethylene manufacture should be considered. In 1985, Sulzer Orthopedics obtained an essentially homogenous calcium stearate-free polyethylene with substantially improved wear behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that the measuring system could not distinguish between wear and creep, or cold flow, but they also confirmed a relatively large initial penetration which they attributed to creep, and found that alumina ceramic femoral heads penetrated more slowly than metal heads into polyethylene cups. Zichner and Willert (1992) questioned the validity of laboratory testing, since the simulator results of Semlitsch et al (1977) had suggested a 20:1 reduction in wear for the ceramic heads. We have now shown that clinical and laboratory simulator results can be in excellent accord.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical advantages of ceramic compared with metal heads are that the smooth finish, hardness, and wettability lead to less friction, more lubrication, and less scratching between the bearing surfaces and thus lower rates of liner wear and osteolysis [37], although this is based on use of historical UHMWPE (gamma air-sterilized polyethylene) and older manufacturing processes of femoral heads that may not generalize to contemporary implants. One of the major concerns about ceramic heads, especially in ceramic-on-ceramic articulation, is the risk of component fracture; however, this has shown to be decreased in ceramic-on-polyethylene bearing surfaces [1,39].…”
Section: Introductionmentioning
confidence: 99%